EXPLORING TEACHING AND LEARNING ENGLISH AT SMAIT NURUL FIKRI - Rina Syafitri Syukur; Rahmiaty; Rusma Setiyana (English Education Department, 2021)
Nowadays, the total number of parents who send their children to the school of Islam Terpadu (IT) increased significantly especially in Aceh. The design of mixed curriculum between general education and religious education became a trigger for parents. The aim of this study is to explore teaching and learning English at one of senior high schools of Islam Terpadu (IT) in Banda Aceh in terms of teaching strategies, media and assessment. This study used qualitative method in nature. Two English teachers who taught at the tenth grade were participated in this study. Observations and interview were conduct to collect the data. The data were analysed and interpreted through qualitative procedures. The findings indicated that teachers used various strategies, media and different assessment in teaching English to motivate the students to learn English. In other hand, talent program stimulated the students to improve their English abilities which are related to religious education. However, the teachers expect to set out the English contents more specifically toward religious education (Qur’an and Hadits).